Embryonic attenuated Wnt/β-catenin signaling defines niche location and long-term stem cell fate in hair follicle - Xu, Zijian (eLife, 2015)
Long-term adult stem cells sustain tissue regeneration throughout the lifetime of an organism. They were hypothesized to originate from embryonic progenitor cells that acquire long-term self-renewal ability and multipotency at the end of organogenesis. The process through which this is achieved often remains unclear. Here, we discovered that long-term hair follicle stem cells arise from embryonic progenitor cells occupying a niche location that is defined by attenuated Wnt/β-catenin signaling. Hair follicle initiation is marked by placode formation, which depends on the activation of Wnt/β-catenin signaling. Soon afterwards, a region with attenuated Wnt/β-catenin signaling emerges in the upper follicle. Embryonic progenitor cells residing in this region gain expression of adult stem cell markers and become definitive long-term hair follicle stem cells at the end of organogenesis. Attenuation of Wnt/β-catenin signaling is a prerequisite for hair follicle stem cell specification because it suppresses Sox9, which is required for stem cell formation. DOI: http://dx.doi.org/10.7554/eLife.10567.001